Prevalence and influencing factors of allergic rhinitis among 6 - 18 years old children in Inner Mongolia Autonomous Region - Xiong SU; Tao YAN; Xing-guang ZHANG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the prevalence and influencing factors of allergic rhinitis (AR) in children aged 6 - 18 years in Inner Mongolia Autonomous Region (Inner Mongolia) and to provide references for prevention, control and treatment of AR in the children. MethodsWith stratified multistage random sampling, a survey was conducted among 66 843 students aged 6 - 18 years from primary and high schools in urban and rural regions of 12 leagues/prefectures of Inner Mongolia during March - October, 2020. A self-designed questionnaire was completed by the students' guardians and the students. ResultsAmong the 62 668 students with valid responses, 10 995 (17.54%) were reported having AR symptoms. The results of unconditional multivariate logistic regression analysis showed that the students with following characteristics were more likely to have self-reported AR symptoms: aged ≥ 13 years, being Mongolian ethnic, with a general or poor living environment, having a meat-based dietary pattern, with family history of allergic diseases, and residing in the northeastern/central/central east/ central west regions of Inner Mongolia; while, the girl students and the students residing in rural or pastoral areas and being obese were less likely to have self-reported AR symptoms. ConclusionThe prevalence rate of AR is high and mainly influenced by gender, age, ethnicity, residential region, living environment, dietary pattern, family history of allergic diseases and obesity among 6 - 18 years old children in Inner Mongolia.